ÂŞIK ENSAR ŞAHBAZOĞLU'NUN HAYATI VE SANATI - ESMEZ, ABDULLAH (Fırat Üniveristesi, 2018)
Âşık edebiyatı, kültürel dönüşüm içerisinde kendini koruma ve devamlılığını sürdürme bakımından birçok sıkıntıyla karşı karşıya kalmıştır. Kars yöresindeki âşıklarımız da bu sıkıntıları yaşamış insanlar olarak bu kültürü gelecek nesillere aktarma açısından önem arz etmektedir. Özellikle usta-çırak ilişkisi veya diğer şekillerde âşıklık elde etmiş birçok şairimiz bu geleneği koruyup sürdürebilmenin uğraşı içerisinde olmuşlardır. Ölçü, kafiye, nazım şekilleri ve türleri gibi birçok unsur bu âşıklar sayesinde gelecek kuşaklara taşınmıştır ve taşınmaya da devam edecektir. Âşık Ensar Şahbazoğlu da bu âşıklar arasında dilinin döndüğünce bu kültüre katkı sağlamaya çalışan ender isimlerden biri olarak kendi güneşinden beslenen şairler arasında yerini almıştır. Anahtar Kelimeler: Âşık Ensar ŞAHBAZOĞLU, Kültürel Dönüşüm, Kars, Usta-Çırak, Mahlas, Atışmalar, Şiir.

Minstrel literature has faced many problems within the process of cultural transformation in terms of self-protection and maintaining continuity. Considering holism of the tradition, it is inevitable to encounter such problems in and around Kars. The region is one of the important locations for minstrelsy tradition. Minstrels grown up in the region are important for handing such culture down the next generations. Especially, many of our minstrels who gained the title of minstrel through master-apprentice relationship or in other ways have endeavored to protect and sustain this culture. Many components such as meter, rhyme, methods and types of poetry are communicated and will be continued to be communicated to the next generations owing to those minstrels. Âşık Ensar Şahbazoğlu, as a precious person trying to contribute to this culture as much as he can among those minstrels, has taken his place among the minstrels who are fueled by their own sun. Key Words: Cultural Transformation, Kars, Master-Apprentice, Pseudonym, Call-and-Response, Poem.
Life and art of Aşık Ensar Şahbazoğlu
Keywords: Türk Dili ve Edebiyatı